Translational Neuroscience Fundamental Approaches for Neurological Disorders - Tuszynski, Mark H. (Springer US : Imprint: Springer, 2016)
Translational Neuroscience offers a far-reaching and insightful series of perspectives on the effort to bring potentially revolutionary new classes of therapies to the clinic, thereby transforming the treatment of human nervous system disorders. Great advances in the fields of basic neuroscience, molecular biology, genomics, gene therapy, cell therapy, stem cell biology, information technology, neuro devices, rehabilitation and others over the last 20 years have generated unprecedented opportunities to treat heretofore untreatable disorders of the nervous system. This book provides a wide-ranging yet detailed sample of many of these efforts, together with the methods for pursuing clinical translation and assessing clinical outcomes. Among the topics covered are Alzheimer's disease, Parkinson's disease, stroke, multiple sclerosis, epilepsy, motor neuron disease, pain, inborn errors of metabolism, brain tumors, spinal cord injury, neuroprosthetics, rehabilitation and clinical trial design/consideration. Translational Neuroscience is aimed at basic neuroscientists, translational neuroscientists and clinicians who seek to gain a perspective on the nature and promise of translational therapies in the current era. Both students and established professionals will benefit from the content.